Combined cycles for CO2-capture with high efficiency. (7th August 2007) - Leithner, Reinhard
The presented paper gives an overview on combined cycles for CO2-capture with high efficiency focussed on processes using a Solid Oxide Fuel Cell (SOFC), because of the air separating ability of the SOFC-membrane. The SOFC-membrane is only permeable for oxygen ions, so the cathode exhaust gas is oxygen depleted air, which should be discharged to the atmosphere after recycling or using the heat via a heat exchanger. Using fuels consisting of hydrocarbons like gasified fossil fuels and biomass or reformed (bio)gas, the anode exhaust gas consists of CO2, water vapour and not used gaseous fuel. If the not used gaseous fuel is separated and recycled instead of being burnt by mixing with the cathode exhaust gas as usual today, CO2 is left as only anode exhaust gas by simply condensing the water vapour. Similar results can be achieved by a mixed conducting membrane and chemical (metal?metal oxide) looping.